The policy of the Russian Empire toward Islam in Turkestan: post-Soviet historiography (Journal of history, 2023)
The abolition of ideological stereotypes allowed the exploration of the Russian Empire's religious policy in Turkestan in new historical conditions. Furthermore, post-Soviet researchers have their own views on this problem. Therefore, this policy reveals positive and negative or hidden aspects. To analyze the essence of the attitude of Russian officials in relation to Muslim institutes historians investigate conditions of waqf properties and education, also the status of Muslim elites. According to some researchers, the emigration of Russian peasants to Turkestan was used to realize cultural assimilation and the baptism of the Muslim people. Experts dicscover the policy of the Russian Empire towards Islam was unstable and linked with various geopolitical factors. Post-Soviet historians consider the complication of socio-economic relations and the decadence of Muslim institutions as the main reasons for the Andijan uprising of 1898. In the conclusion, the historiographical results of the problem are summed up, general results and disputable sides of the issue under consideration are analyzed. Besides the problematic aspects of the topic under consideration are indicated for the purpose of further study.